Trójca Święta w „Hymnach kościelnych” i w pieśniach kościelnych - Breza, Edward (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The author has been for a longer time making excerpts from church hymns used in Roman Catholic priests’ prayers (breviaries) and liturgy, as well as in church songs. The excerpted material relates to (artistic) designations of Mother of God, Christ, Holy Ghost, and the Saints (cf. footnotes in the article). In this way, the article describes the names of persons in the Holy Trinity. The collection is of use as philological documentation, for historical research in European and Polish piety, and as help for preachers, religious instructors, and Christian literary authors.